Comparison of Recovery Rate and Early Complications Between Primary Resection and Two-stage Operation in the Treatment of Acute Non- Complicated Sigmoid Volvulus (Journal of Rangpur Medical College, 2024)
Background: This study compares recovery rates and early complications associated with primary resection and a two-stage operation in treating acute sigmoid volvulus, a gastrointestinal emergency requiring prompt intervention. Proper diagnosis and appropriate operative approaches are crucial for lifesaving treatment. Objectives: This study was aim to compair of recovery rate and early complecations between two operative procedures. Methods: The cross-sectional analytical study was conducted from May to October 2015in National Institute Cancer Research and Hospital, Mohakhali, Dhaka, Bangladesh, involved 50 patients with acute non-complicated sigmoid volvulus, randomly divided into two groups, with the outcome variable being the only difference between two groups. Results: Two stage operation patients experienced 24% stomal complications, while one stage operation patients did not experience any late complication. The mean time for one stage operation was longer, and one stage operation resulted in 200 ml blood loss compared to 156 ml in two stage operations. Conclusion: In consideration of anastomotic leakage, operative time, operative blood loss post-operative hospital stay, two stage operation was better than primary resection.J Rang Med Col. March 2024; Vol. 9, No. 1: 59-64